Vitamin D3 eradicates Helicobacter pylori by inducing VDR-CAMP signaling - Zhang, Ye; Wang, Chunya; Zhang, Li; Yu, Jie; Yuan, Wenjie; Li, Lei (Frontiers in Microbiology, 2022)
Background: Vitamin D3 (VitD3, 1,25 (OH)2D3) is known to have immunomodulatory and anti-microbial properties; however, its activity against Helicobacter pylori is unclear. In this study, we established H. pylori infection models in wild-type and VitD3 receptor (VDR) knockdown mice and analyzed the effects of VitD3 and their underlying mechanisms. Methods: VDR+/+ and VDR+/- mice were intragastrically infected with the H. pylori SS1 strain. After confirmation of H. pylori infection, mice were treated with different doses of VitD3. The infection levels in stomach tissues were quantified using the colony-forming assay, and the expression levels of the VDR and cathelicidin antimicrobial peptide (CAMP) in the gastric mucosa were analyzed by immunohistochemistry and western blotting. Results: The gastric mucosa of VDR+/- mice was more susceptible to H. pylori colonization and had lower levels of VDR and CAMP expression than that of VDR+/+ mice. H. pylori infection upregulated VDR and CAMP expression in the stomach of both wild-type and mutant mice, and VitD3 treatment resulted in further increase of VDR and CAMP levels, while significantly and dose-dependently decreasing the H. pylori colonization rate in both mouse groups, without affecting blood calcium or phosphorus levels. Conclusion: Our data indicate that oral administration of VitD3 reduces the H. pylori colonization rate and upregulates VDR and CAMP expression in the gastric mucosa, suggesting a role for VitD3/VDR/CAMP signaling in the eradication of H. pylori in the stomach. These findings provide important insights into the mechanism underlying the anti-H. pylori activity of VitD3 and should be useful in the development of measures to eradicate H. pylori.